STEM Lesson Supplementary Activities for Primary School Students: Corn Pudding for Health and Second Career Promotion - Suttiwan, Wanna; Kaewmoongkun, Sutthida; Nokmueang, Yupaporn; Suttiwan, Witsanu (Journal for Developing the Social and Community, 2025)
Background and Aims: Education in the 21st century must cultivate students’ holistic competencies in alignment with the Sustainable Development Goals (SDGs) and following the principles of STEM education. This study aimed to design and assess the appropriateness of a STEM supplementary learning activity titled “Corn Pudding for Health and Second Career Promotion” for primary school students. Methodology: A mixed methods research design was employed, including document analysis, expert panel consultations, and activity evaluation. The research participants consisted of seven individual university lecturers and experts in primary education. A six-domain activity evaluation form was used as the research instrument, and data were analyzed using mean and standard deviation. Results: The designed STEM activity followed the seven-step contextual STEM framework and focused on integrating interdisciplinary knowledge to create a health-oriented corn pudding product. Students engaged in scientific inquiry, applied technological skills, and participated in collaborative classroom activities that reflected real-life situations. The activity also promoted health awareness through appropriate and sufficient dietary practices. The overall appropriateness of the activity was rated at a very high level (M=4.60, SD=0.06). Conclusion: The activity was found to be effective in enhancing students’ nutritional knowledge, scientific skills, design thinking, and awareness of potential second careers. It demonstrated the value of a structured interdisciplinary approach to primary education.